Notes on Early Land Plants Today. 47. Transfer of Iwatsukia to Odontoschisma (Cephaloziaceae, Marchantiophyta) - Gradstein, S. Robbert; Aranda, Silvia Calvo; Vanderpoorten, Alain (Phytotaxa, 2014)
The genus Iwatsukia (Cephaloziaceae) is a small tropical liverwort genus of 4 species, Iwatsukia exigua from Sabah and New Guinea, Iwatsukia bifida from Venezuela and Costa Rica, the pantropical Iwatsukia jishibae, and Iwatsukia spinosa from Venezuela (Schuster 1968, 2002). Vilnet et al. (2012) showed that Iwatsukia jishibae is nested in Odontoschisma (Dumortier 1831: 68) Dumortier (1835: 19) and Váňa et al. (2013) made the necessary nomenclatural transfer. In the framework of a phylogenetic and taxonomic study of Odontoschisma and related genera which is in preparation, we were able to confirm the position of Iwatsukia jishibae in Odontoschisma. In addition, we found that Iwatsukia bifida is nested in Odontoschisma, forming a separate lineage within the genus together with Iwatsukia jishibae. We also found that Iwatsukia exigua, the type species of Iwatsukia, is a synonym of Iwatsukia jishibae. We therefore transfer the genus Iwatsukia to Odontoschisma.